2011
DOI: 10.1007/s00454-011-9378-0
|View full text |Cite
|
Sign up to set email alerts
|

Topology of Random 2-Complexes

Abstract: We study the Linial-Meshulam model of random two-dimensional simplicial complexes. One of our main results states that for p n −1 a random 2-complex Y collapses simplicially to a graph and, in particular, the fundamental group π 1 (Y ) is free and H 2 (Y ) = 0, asymptotically almost surely. Our other main result gives a precise threshold for collapsibility of a random 2-complex to a graph in a prescribed number of steps. We also prove that, if the probability parameter p satisfies p n −1/2+ , where > 0, then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 17 publications
3
76
0
Order By: Relevance
“…The random simplicial complexes of [15], [17] are d-dimensional, have the complete (d − 1)-skeleton and their randomness shows only in the top dimension. Some interesting results about the topology of random 2-complexes in the LinialMeshulam model were obtained in [1], [3], [5].…”
Section: Introductionmentioning
confidence: 96%
“…The random simplicial complexes of [15], [17] are d-dimensional, have the complete (d − 1)-skeleton and their randomness shows only in the top dimension. Some interesting results about the topology of random 2-complexes in the LinialMeshulam model were obtained in [1], [3], [5].…”
Section: Introductionmentioning
confidence: 96%
“…Brown, Erdős and Sós [6] showed that there are 2-dimensional complexes on n vertices with as many as Ω(n 5/2 ) triangles that do not contain a subcomplex homeomorphic to the 2-sphere S 2 , i.e., that do not contain K 2 4 as a topological minor. 7 Thus, the analogue of Conjecture 2 fails for topological minors.…”
Section: Topological Minorsmentioning
confidence: 95%
“…By contracting the edge uv, we obtain the complex Y on Figure 1: Closing a hole by contracting an edge. 7 A simple alternative proof of this is due to Linial (personal communication) and uses a random complex X 2 (n, cn −1/2 ) with small alterations the right, which is a subdivided triangle. Now consider the complete 2-complex K 2 7 on seven vertices.…”
Section: Contractions and Nevo's Minorsmentioning
confidence: 96%
See 1 more Smart Citation
“…
Theorem 27 from our article [1] states that any closed triangulated surface S is balanced, i.e. μ(X ) ≥ μ(S) for any subcomplex X ⊂ S. Here the notation μ(Y ) stands for the ratio v/ f where v and f are the numbers of vertices and faces (i.e.
…”
mentioning
confidence: 99%